Pengaruh gaya hidup, literasi keuangan, dan sosial ekonomi orang tua terhadap pengelolaan keuangan pribadi mahasiswa manajemen keuangan syariah 2018 - Arifin, Danisa Cornellia; Bachtiar, Jusuf (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research is based on students' problems in managing finances. The most basic competencies that must be understood by every student are planning, management, and financial control activities. This research is quantitative with the type of explanatory research. Sources of data used are primary data obtained from the results of the questionnaire. The research sample amounted to 50 students. data analysis applied multiple linear regression. The results of the study simultaneously that Lifestyle, Financial Literacy, and Parents' Socio-Economic have a significant effect on Students' Personal Financial Management. While partially Financial Literacy has a significant effect on Student Personal Financial Management. Meanwhile, Parents' Socio-Economic and Lifestyle have no significant effect on Students' Personal Financial Management.